Exploration of learning strategies in the social studies based on the Merdeka Curriculum - Susy Suari; Junaidi Indrawadi; Fadilla Syahriani (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The objective of this study is to explores innovative social studies teaching strategies within the framework of the Merdeka Curriculum in Indonesia, aiming to enhance the effectiveness of social studies education. Utilizing a methodological approach that combines qualitative and quantitative methods such as classroom observations, teacher interviews, and student surveys the research evaluates the implementation and impact of various teaching strategies. The findings indicate that effective integration of these strategies can create a more dynamic and engaging social studies curriculum. The Merdeka Curriculum, emphasizing freedom and flexibility in education, offers a unique opportunity to integrate teaching methods tailored to the evolving needs of students. This research focuses on four main strategies: Project-Based Learning, Inquiry-Based Learning, Collaborative Learning, and Experiential Learning. Each strategy is analyzed for its potential to foster critical thinking, engagement, and the application of social studies concepts in real-world contexts. Project-Based Learning is examined for its ability to connect academic content with real-world issues and develop students' problem-solving skills. Inquiry-Based Learning is analyzed for its role in promoting students' curiosity and independent research. Collaborative Learning is explored for its effectiveness in building teamwork and communication skills. Experiential Learning is evaluated for its capacity to provide hands-on experiences that deepen students' understanding of social concepts. This research integrates these strategies into social studies education by aligning teaching methods with Merdeka Curriculum principles, educators can create a more responsive and impactful learning environment that meets the diverse needs of students and prepares them to be active citizens in an increasingly globalised world